# Differential equations?

I've worked this out but not too sure if I've done it right.. Would like to see how others would work it out..

Show that the function f(t) = 3/2et2 - 1/2 is a solution to the differential equation y1 - 2ty = t

### 1 Answer

Relevance

- GraduateLv 410 years agoFavourite answer
You do this by separation of variables.

The equation is :

dy/dt - 2ty = t

So

dy/dt = t (2y +1)

And thus

{ 1/ (2y+1) }dy = t dt

(1/2) ln (2y + 1) = (1/2) t^2 + C

So

ln (2y + 1) = t^2 + 2C

(2y + 1) = e^(t^2 + 2C) = e^(t^2) * D where D=e^(2C)

Rearranging,

y = (D/2)e^(t^2) - 1/2.

In particular, when D=3,

y= f(t) = (3/2)e^(t^2) - 1/2 (shown)

Regards

Edem

Still have questions? Get answers by asking now.